Paleo-depth of fossil faults estimated from paleostress state: Applications from the Alps and the Apennines (Italy). (November 2020) - Federico, Laura; Maino, Matteo; Capponi, Giovanni; Crispini, Laura
Abstract: Estimating the paleo-depth of a fossil fault usually requires the application of complex and highly specialized techniques. We propose a new method, that is based mainly on field data and simplifies the process: - calculation of the reduced stress tensor (with four variables) through inversion of fault-slip data; - calculation of the complete stress tensor (i.e., the two remaining unknowns) using the friction and the rupture laws; - estimation of the paleo-depth. The friction law is defined by the lower boundary of the cloud of points in the Mohr space represented by inherited faults. This operation fixes the abscissa origin of the Mohr diagram. To calculate the rupture law, we estimate both intact rock and outcrop quality parameters and need pairs of conjugate faults. Their dihedral angle fixes a point on the Mohr circle, where the rupture law has to be tangent, thus defining the scale of the axes and the values of the principal stresses. To define the paleo-depth, we estimate the average density of overlying rocks and the hydraulic conditions (i.e. the pore pressure).Testing of this workflow in three well-constrained geological case studies proved its promising reliability, showing a good agreement with independent stratigraphic and structural evidence. Highlights: This new method can estimate depth of activity of fossil faults from field data. Fault-slip data, including reactivated faults and conjugate faults are needed. Paleostress tensors are calculated through inversion of fault-slip data. The friction and rupture laws are calculated to constrain paleostress values.